Studying flame-retardancy, smoke and toxicity of fiber-reinforced composites manufactured via modified resins and metallic coatings - Md Shafinur Murad; Abdulhammed K. Hamzat; Eylem Asmatulu; Ersin Bahçeci; Mete Bakir; Ramazan Asmatulu (Hybrid Advances)
This study focuses on the development of flame-retardant fiber-reinforced polymer (FRP) composites, which are typically fire-intolerant despite their excellent mechanical, chemical, and thermal properties. Incorporating modified resins, metallic surface coatings, and graphene powder improved the composite's fire resistance and reduced smoke emissions properties. The composites were fabricated using a wet-layup process under vacuum. Thermal stability, flammability, and smoke production characteristics were evaluated using differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), thermomechanical analysis (TMA), UL94 vertical flame test, and standardized smoke and toxicity tests. The addition of 9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (DOPO) and Cu film surface coating led to superior smoke suppression with negligible smoke production (maximum Ds of 0–4, VOF4 of 1 at 180–240 s), whereas unmodified composites showed significant smoke development (maximum Ds of 759 at 240 s, VOF4 of 1157). Because DOPO and matrix interacted to form a char layer, the modified test samples passed the UL 94 vertical flame tests with a V0 rating. The metal films also enhanced fire-shielding and heat-dissipation, which resulted in a synergistic effect of chemical and physical protection with minimum release of toxic gases. This research could lead to composites with reduced emissions of harmful gases and minimal smoke formations with better fire-retardant properties.